(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
The current study is aimed to estimate the diagnostic reference dose levels (DRLs), the volume computer tomogram dose index (CTDIvol), the CT air kerma-length product (PKL,CT) and the effective dose (E) for head, chest and chest-abdomen-pelvic CT examinations performed on adults in King Abdullah Medical City (KAMC), Saudi Arabia. Demographic parameters (such as age, gender, weight, height) for a sample of 535 computed tomography (CT) patients and physical scan parameters (such as patient tube voltage (kV), reference and effective mill ampere-second (mAs), scan length, number of slices, and pitch factor) were collected from a picture archiving and communication system (PACS). CTDIvol and PKL,CT were studied for different patients weights (40 -60 kg, 60-80 kg, 80-100 kg and 100-120 kg). Mean CTDIvol, PKL,CT and effective dose for a standard weight (70 kg ±10%) was evaluated according to the three CT protocols considered and the results were, as follows: for head examinations – 61.8 mGy, 1212 mGy.cm and 2.55 mSv, respectively; for chest examinations- 13.1 mGy, 657.5 mGy.cm and 9.21 mSv, respectively; for chest-abdomen-pelvic examinations - 13.9 mGy, 782.5 mGy.cm and 11.73 mSv, respectively. The effective dose for the chest examinations was lower than the corresponding value communicated by the European study group under European Commission. The effective dose for head examinations, was slightly higher than the one communicated by the European Commission study due to differences in the scan length. It needs optimizing the radiation dose delivered to patients via periodical review of scan parameters for a protocol under study.